Adenosine Kinase Contributes to Cytokinin Interconversion in Arabidopsis(1)([W])([OA]) - Schoor, Sarah (American Society of Plant Biologists, 2011)
Purine salvage enzymes have been implicated, but not proven, to be involved in the interconversion of cytokinin (CK) bases, ribosides, and nucleotides. Here, we use Arabidopsis (Arabidopsis thaliana) lines silenced in adenosine kinase (ADK) expression to understand the contributions of this enzyme activity to in vivo CK metabolism. Both small interfering RNA- and artificial microRNA-mediated silencing of ADK led to impaired root growth, small, crinkled rosette leaves, and reduced apical dominance. Further examination of ADK-deficient roots and leaves revealed their irregular cell division. Root tips had uneven arrangements of root cap cells, reduced meristem sizes, and enlarged cells in the elongation zone; rosette leaves exhibited decreased cell size but increased cell abundance. Expression patterns of the cyclinB1;1::β-glucuronidase and Arabidopsis Response Regulator5::β-glucuronidase reporters in the ADK-deficient background were consistent with altered cell division and an increase in CK activity, respectively. In vivo feeding of ADK-deficient leaves with radiolabeled CK ribosides of isopentenyladenosine and zeatin showed a decreased flux into the corresponding CK nucleotides. Comprehensive high-performance liquid chromatography-tandem mass spectrometry analysis detected significantly higher levels of active CK ribosides in both sense ADK and artificial microADK. Taken together, these metabolic and phenotypic analyses of ADK-deficient lines indicate that ADK contributes to CK homeostasis in vivo.